Convalescent Plasma Therapy for pregnant patients with COVID-19: Case Series - Ayed, Mariam; Alshammari, Farah; Ayed, Amal; Gadalla, Ibrahim; Aldoohan, Fawaz; Alsharidah, Sondos (International Journal of Innovative Research in Medical Science, 2021)
Aim: The objective of this study is to report the effect of COVID-19 convalescent plasma (CCP) therapy in pregnant women with moderate or severe COVID-19 infection. Methods: This study is a case series of 9 pregnant women with moderate or severe COVID-19 infection. All the patients (N=9) received two doses (400 mL) of ABO compatible CCP. The median gestational age at the time of confirmed COVID-19 diagnosis was 31 weeks (range: 16-39 weeks). Results: No adverse events with CCP were reported. On day 3 post-CCP administration, there was a significant improvement in oxygen saturation (p=0.032), decrease in the respiratory rate from baseline (p=0.041), and improvement in the lymphocyte counts (p=0.043). None of the patients required invasive ventilatory support or extracorporeal membrane oxygenation and all were discharged home (median time from CCP administration to discharge was 6 days). All the patients gave birth to healthy newborns. The newborns had negative SARS-CoV-2 PCR on days 2 and 5 of ages. Conclusion: Our case series demonstrated CCP therapy to be safe with improved clinical outcomes during moderate and severe COVID-19 infection in pregnancy. However, extensive studies are still needed to recommend the routine use of CCP in the pregnant population with COVID-19 disease.